Terapi Bekam Basah Terhadap Penurunan Kadar Asam Urat Dalam Darah: Tinjauan Pustaka: Wet Cupping Therapy for Reducing Uric Acid Levels: Literatur Review - Arif Tirtana; Muhammad Habib (Journal of Health, 2023)
Uncontrolled uric acid on blood can lead to hyperuricemia in a person. Many symptoms shown when a person suffer gout were inflammation, pain, heat, swollen and stiff joints so it cannot move as usual. The morbidity rate of patients at the age of 34 years was 32% and aged over 34 years was 68%. One of the solutions that can be offered to reduce the symptoms of gout is by treating was removing static blood that contains toxins from the human body. The research aim was to determine the effect of wet cupping on reducing uric acid levels in the blood. The method that used on this research was Problem Intervention Comparison Outcome Study design (PICOS) framework. The selection of articles with the keywords "gout" and "cupping" found 1627 journals. Total of 32 data do not match the formulation of the problem and objectives. While 312 data do not match the title. Journals that match the inclusion criteria obtained 8 studies. The literature used is the Google Scholar database, Springer Link, Science direct. The results of the assessment of 8 journals, found that wet cupping can reduce uric acid levels in the blood with a significant value (P <0.05).